A broadband sound absorber of hybrid-arranged perforated panels with perforated partitions. (January 2022) - Wang, Shuai; Li, Fengming
Highlights: A novel sound absorber of hybrid-arranged perforated panels is proposed and designed. Acoustic impedance of the structure is derived by the equivalent circuit method. Sound absorption coefficient of the proposed model shows a significant improvement. Experiments are conducted to validate the accuracy of the theoretical model. Abstract: Several parts of panels with different perforated characteristics and cavity depths are integrated to present a novel hybrid-arranged perforated panel with perforated partitions. Perforated panels in the same layer are divided by perforated partitions. By designing the parameters of the perforated panels and the depths of the air cavities, the sound absorption coefficient (SAC) of the structure can be greatly enhanced. The equivalent circuit method (ECM) is applied to analyze the acoustic impedance of the structure. An acoustic experiment and numerical simulations by the finite element method are carried out to validate the results of the proposed analytical model. From the investigations, it is found that the SAC of the model has not only a wideband but also a high sound absorption level. The hybrid-arranged perforated panel with perforated partitions provides a new way to design sound absorbers for practical applications.